LEUKEMIA LIMFOBLASTIK AKUT PADA DEWASA DENGAN FENOTIP BILINEAGE (LIMFOID-B DAN T) - Maimun Z A; Budiman Budiman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
In this report we describe a patient with adult acute lymphoblastic leukemia with bilineage phenotypic. He was found to have massive right pleural effusion with mediastinal shift to the contra lateral side. There was also a smaller left pleural effusion. He had multiple bilateral cervical lymphadenopathy, tense ascites and bilateral pedal oedema up to the shins. He was otherwise clinically stable.His full blood count on admission showed Hb of 11.4 g/dl, platelets of 59 X 109/L and WBC of 12.99 × 109/L with blasts of 26%. His renal function was normal with a creatinine of 107 micromoles/L. Bone marrow trephine biopsy showed features consistent with acute lymphoblast leukemia-L1. Flow cytrometry of his blood was suggestive of bilineage phenotypic acute lymphoblast leukaemia. It showeda single population of blasts (about 31%) which expressed cCD3+, CD4-, CD7+, CD5-, CD19+, CD34+, TdT+, cytoplasm IgM, CD79a+ and 30% are CD10+, and there was aberrant CD33+ expression with no evidence of MPO or CD117 expression. Cytogenesis of the bone marrow trephine biopsy showed numerical and structural abnormalities in nine out of the seventeen cells analysed. These abnormalitiesare 43 47,XY, add (1)(p34.2), add(2)(p13), i(17)(q10), +21[cp9].